Los cien primeros días de Moñino en Roma - Enrique Giménez López (Mélanges de la Casa de Velázquez, 2009)
There is unanimous agreement that Jose Monino's work as ambassador in Rome was decisive for the downfall of the Company of Jesus. And yet the process was complete by the end of the ambassador's first hundred days in the Eternal City, only minor issues remaining to be settled, which detained him there until July 1773. This article gives a sequential account of Monino's diplomatic activity and looks in detail at the substance of his audiences with the Pope and his interviews with the ambassadors of France, Naples and to a lesser extent Portugal, all of whom were desirous of securing the abolition and moved under Monino's direction.